Green warehouse performance monitoring system design using analytical hierarchy process and supply chain operation reference - Muttaqin, P S; Margareta, W; Zahira, A D (ASCEE, 2022)
The use of logistics service providers in Indonesia progressively increasing from year to year, especially XYZ company as warehouse service providers with main activity are product distribution and storage of finished good. Currently, the XYZ company uses a web-based system to record products in warehouse activities, but this system has not been able to measure and evaluate warehouse performance. In addition, the company has large operating cost caused by product handling costs and warehouse operating costs. In this study, a monitoring system was designed that can measure and evaluate warehouse performance to be a sustainable warehouse. Therefore, this study integrates Supply Chain Operation Reference (SCOR) and Analytical Hierarchy Process (AHP) by considering green warehousing criteria. The weighting of importance level of each criteria using AHP method results in make criteria getting a weighted score (0.421), plan (0.213), deliver (0.152), source (0.119), return (0.064), and environment (0.032). The results of the scoring system using OMAX show that 7 KPIs are included in the green category, yellow category (11 KPIs), and red category (10 KPIs). Total value the company's green warehouse performance index is 11.15 which indicates that overall warehouse performance has not reached expected performance based on Traffic Light System Method.